Effect of the seedling age and Compost to the growth of Palm Date Lulu (Phoenix Dactylifera L.) Nursery and Investigation of Female Seedling on Soil of Sub-Optimal Land - Siti Masreah Bernas; Maria Fitriana; Andi Wijaya; Siti Nurul Aidil Fitri (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2020)
Bernas SM, Fitriana M, Wijaya A, Fitri SNA. 2020. Effect of the seedling age and compost to the growth of palm date lulu (Phoenix Dactylifera L.) nursery and investigation of female seedling. Jurnal Lahan Suboptimal : Journal of Suboptimal Lands 9(2): 199-207.Indonesia imported very high amount of date palm fruits about 9.99 million kg or US 13.18 M, because of that it is necessary to develop a research about date palm seedling nursery and investigation of female date, since this is a dioecious plant. The aim of this investigation was to find out characteristics of female date seedling and the effects of seedling age and compost on seedling growth. There were 2 steps in this research: the first was application of compost on seedling (without and plus compost treatments) and the age of seedling (15 and 30 days old) for transplanting into polybag, the growth ability of plant was monitored. The second step was transplanting seedling at 30 days old into pan for investigation female date, which 20 seedlings were planted in one pan and replicated 3 times.Â Results showed that compost increased roots and leaves growth on seedling.Â Transplanted at 30 days old seedling had the ability to grow about 95% compared to 15 days old was only 45%. It was found that female seedling was about 25% and the rest (75%) was male or sterile. It is needed further investigation on growing female seedling in the field and can it produce fruit.